A global overview of residential building energy consumption in eight climate zones. Issue 1 (2nd January 2016) - Bohne, Rolf André; Huang, Lizhen; Lohne, Jardar
Abstract: This study provides a global overview and comparison of residential building energy consumption (RBEC) in 8 climate zones in order to provide a visible foundation for policymakers and decision-makers with respect to sustainable future levels of RBEC. A total of 31 countries and 14 provinces/municipalities within these 8 climate zones are furthermore grouped into 20 different regions based on income. Demographic statistics regarding housing and RBEC of these regions are collected for analysis in this study. The results indicate that: 1) RBEC per capita and per m 2 in most Organisation for Economic Co-operation and Development (OECD) countries has decreased over the past two decades; 2) in developing countries, such consumption does not follow the same pattern of change; 3) within each climate zone, RBEC per m 2 is not significantly different for regions and countries in the same income groups, but there is significant difference in RBEC per capita for different regions and countries, even within the same climate zone and income group; and 4) RBEC per capita and per m 2 in the same climate zone differ widely between different income groups.